Epidemic of lower extremity peripheral arterial disease in China: current trends and future prediction - Yu, Jianxing; Zhang, Yuhan; Zhang, Qingqing; Wang, Jinyi; Gu, Aiqin; Wei, Jing; Zhang, Chuanmeng (Frontiers in Cardiovascular Medicine, 2025)
BackgroundLower extremity peripheral arterial disease (PAD) reflects the overall condition of the cardiovascular system. Due to its often asymptomatic nature, PAD is frequently overlooked. We aimed to estimate the disease burden of PAD in China over the past 30 years and to project future trends over the next 25 years.MethodsThe incidence and disability-adjusted life years (DALYs) of PAD was extracted from the Global Burden of Disease (GBD) database and subsequently described. Joinpoint regression was used to assess trends from 1990 to 2021, and an age-period-cohort model was constructed to examine the influence of period and cohort effects on incidence and DALYs of PAD. A Bayesian APC model was also applied to forecast trends through 2046.ResultsIn 2021, the annual number of new PAD cases in China was 2.45 (95% UI: 2.11–2.85) million, of which 1.74 (1.50–2.03) million were female and 0.71 (0.61–0.83) million were male. The number of new cases in 2021 was obviously higher than that in 1990 among females and males. The age-standardized incidence rate (ASIR) exhibited an increasing trend among males, while a decreasing trend was observed among females. Incidence number rose across all age groups, but rates declined in females. Period effects were identified as high-risk factors for PAD incidence and in both sexes, whereas the cohort effects appeared protective. The number of new cases is projected to rise from 2.45 million in 2021 to 4.04 million by 2046, while the ASIR remains stable. Trends in DALYs showed similar patterns.ConclusionThe burden of PAD in China has increased markedly from 1990 to 2021 and is expected to continue rising over the next 25 years. Efforts to reduce modifiable risk factors-such as smoking and metabolic diseases-and to enhance PAD prevention and management, including the establishment of Pan-Vascular Management Center, are urgently needed.